2021
DOI: 10.12688/f1000research.46883.1
|View full text |Cite
|
Sign up to set email alerts
|

Current status of insecticide resistance in malaria vectors in the Asian countries: a systematic review

Abstract: Background: The application of insecticides for malaria vector control has remained a global problem, due to the current trend of increased resistance against these chemicals. This study aims to determine the insecticide-resistant status in Asia and how to implement the necessary interventions. Moreover, the implications of resistance in malaria vector control in this region were studied. Methods: This systematic review was conducted using a predefined protocol based on PRISMA-retrieved articles from four scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This study retrieved articles from four science databases, namely ProQuest , Science Direct , EBSCO , and PubMed , from December 2009 to December 2019. A systematic review was conducted using a predefined protocol based on the preferred reporting items for systematic reviews and meta-analyses (PRISMA) 11 , 12 . The searching process utilized four main combinations of the following keywords: “malaria”, “vector control”, “insecticide”, and “Asia”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study retrieved articles from four science databases, namely ProQuest , Science Direct , EBSCO , and PubMed , from December 2009 to December 2019. A systematic review was conducted using a predefined protocol based on the preferred reporting items for systematic reviews and meta-analyses (PRISMA) 11 , 12 . The searching process utilized four main combinations of the following keywords: “malaria”, “vector control”, “insecticide”, and “Asia”.…”
Section: Methodsmentioning
confidence: 99%
“…Figshare: PRISMA checklist for ‘Current status of insecticide resistance in malaria vectors in the Asian countries: systematic review’. https://doi.org/10.6084/m9.figshare.13582517 12 .…”
Section: Data Availabilitymentioning
confidence: 99%
“…Studies have shown that insecticide resistance in malaria vector population is a global phenomenon, which is highly predominant in the sub-Saharan Africa (Kleinschmidt et al, 2018) [13] . Resistance has been reported in all the classes of insecticides recommended by WHO for public use namely; pyrethroids, organochlorines, carbamates and organophosphates (Susanna and Pratiwi, 2022; WHO, 2018) [26,28] . Significant amount of resistance was found in both DDT and pyrethroid in the present study, and this is consistent with the study by Nwankwo et al (2017) [19] in Amansea, Anambra State.…”
Section: Mortality Rate and Susceptibility Statusmentioning
confidence: 99%
“…The malaria control and elimination programme now relies mainly on two vector intervention tools, long-lasting insecticidal nets (LLINs) and indoor residual spraying (IRS), that use insecticides to mitigate malaria transmission. The emergence of Anopheles strains resistant to currently used insecticides poses a critical challenge to achieving malaria elimination by 2030 [ 2 , 3 ]. Vector control is an essential aspect of the program to combat malaria transmitted by Anopheles .…”
Section: Introductionmentioning
confidence: 99%